Pemanfaatan IoT untuk Efisiensi Energi pada Pabrik Pintar: Tantangan, Solusi dan Tren Teknologi - Suciana, Ewin; Nasrullah, Muhammad Hudzaifah; Christanto, Duta Arief; Cahyadi, Dede; Giantri, Lilik Tiara (Jurnal Teknologi Terpadu, 2025)
This study investigates the role of the Internet of Things in enhancing energy efficiency within smart factories by analyzing current trends, driving factors, and challenges. A Systematic Literature Review with the PRISMA framework was employed to ensure systematic and comprehensive selection of studies. The PICO framework guided the formulation of research questions, facilitating rigorous screening of data sourced from the Scopus database with strict inclusion and exclusion criteria. Findings reveal a substantial increase in IoT-related energy efficiency research in smart factories between 2019 and 2025. Key challenges identified include high sensor energy consumption, communication reliability, and network management complexity. Research limitations stem from the exclusive use of the Scopus database and English-language publications. The study highlights the necessity of interdisciplinary approaches and advanced technologies such as 5G and edge computing to address integration and data security issues, thereby supporting the effective and sustainable deployment of IoT in the manufacturing sector.